Prevalence and determinants of vulnerability among Sundarbans mangrove forest resource-dependent communities in cyclone-prone southwestern coastal districts of Bangladesh - Md. Tanvir Hossain; Tunvir Ahamed Shohel; Md. Nasif Ahsan; Md. Nazrul Islam (Trees, Forests and People)
Vulnerability assessment is crucial for reducing the impact of natural disasters on marginalized coastal communities. In Bangladesh, studies have addressed the vulnerability of coastal populations, but they often overlook the Sundarbans mangrove forest resource-dependent communities (SMFRDCs). These marginalized groups, reliant on the forest, frequently face natural disasters such as cyclones, increasing their vulnerability. This study seeks to assess the extent of vulnerability among SMFRDCs and uncover the critical risk factors contributing to it. This cross-sectional survey was conducted in three southwestern coastal districts of Bangladesh: Satkhira, Khulna, and Bagerhat. Data were collected from 782 SMFRDCs in three Upazila (sub-district) of selected coastal districts using a structured interview schedule (SIS) and following a multistage stratified random sampling approach. The data were analyzed using IBM SPSS Statistics v27 for Windows. A one-sample binomial test was performed to assess the prevalence of vulnerability. Additionally, bivariate analyses (Pearson’s Chi-square [χ2], Yates’s Correction for Continuity [χ2Yates], Phi [φ], and Cramer’s V [φc]), and multivariable binary logistic regression (MBLR) were conducted to identify the associated risk factors. The findings of the one-sample binomial indicate that among the coastal Upazila, the vulnerability prevalence was highest in Mongla (53.4 %; 95 % CI: 47.4 % - 59.3 %). Additionally, honey collectors were found to be more vulnerable to natural disasters, with a prevalence of 60.8 % (95 % CI: 52.7 % - 68.6 %) among the SMFRDCs. The MBLR findings indicate that SMFRDCs with over 31 years of experience and involvement in multiple occupations were less vulnerable to natural disasters. Likewise, SMFRDCs with better household materials, transport, and livestock assets were less vulnerable to natural disasters. In contrast, those with medium-to-high domestic assets were more at risk. Additionally, having land and access to loans reduced the likelihood of vulnerability. SMFRDCs with better natural, physical, and political capital were also less vulnerable. The findings show that vulnerability among SMFRDCs varied by geospatial location and occupation. Socio-demographics, household resources, and livelihood capitals were key predictors of the household vulnerability of SMFRDCs. To reduce this vulnerability, it is recommended that organizations – governmental and non-governmental – work together to create comprehensive plans involving SMFRDCs in both planning and implementing disaster risk reduction strategies by addressing individual and community-level factors.